Frameworks, methodologies, and tools for developing rich Internet applications - Alor-Hernandez, Giner, 1977-; Rosales-Morales, Viviana Yarel, 1986-; Colombo-Mendoza, Luis Omar, 1987-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book presents current research and analysis on the use of JavaScript and software development to establish new programs intended for the Web, offering an in-depth look at computer and Web programming"--Provided by publisher.
Basic concepts on RIAs -- Frameworks for RIAs development -- Software development methodologies for traditional web applications and RIAs -- Important factors on RIAs development -- Multimedia support for native/embedded video playback on frameworks for RIAs development -- Aspect-oriented programming (aop) support on RIAs development -- Design patterns support for RIAs development -- UI Patterns support on RIAs development -- Case studies using JavaScript-based frameworks -- Case studies using Adobe Flex -- Case studies using JavaFX -- Multi-device RIAs development -- An overview of RIAs development tools -- AlexandRIA: a visual tool for generating multi-device RIAs -- New trends on RIAs development.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 11/05/2014).
Keywords: Internet programming; Web applications; Web site development; JavaScript (Computer program language); Application software -- Development; Software frameworks; Aspect-oriented programming; E-commerce; E-learning; JavaScript; Multimedia content; Software development; Web engineering; Electronic books